THE IMPLEMENTATION OF PRACTICE-REHEARSAL PAIRS STRATEGY TO IMPROVE ENGLISH SPEAKING SKILLS AT THE EIGHT GRADE OF MA DDI KABALLANGANG - Mutmainnah, Mutmainnah; Mujahidah, Mujahidah (Inspiring: English Education Journal, 2019)
The purpose of this research was to find out the implementing practice-rehearsal pairs strategy in improving students? speaking skills at the eight grade of MA DDI Kaballangang. The results of the research are useful for the teachers and the students because they will get a new strategy that is effective to be used in the English learning process especially in improving speaking. The subject of this research was XI IPA class which is consisted of 21 students. The sample was taken by using purposive sampling. The design in this research was pre-experimental with pre-test and post-test design. The researcher gave pre-test and post-test to know whether implementing practice-rehearsal pairs strategy can improve students? speaking skills or not.  The result of this research was indicated that there was an improvement of the students? speaking skills. It was indicated by the students? mean scoreof post-test (65.10) was greater than pre-test (30). Even, for the level significant (p) 5% and df = 21, and the value of the table is 1.725, while the value of t-test is 3.45. It means that the t-test value is greater than t-table (3.45 ? 1.725). Thus, it can be concluded that the students? speaking skills are significantly better after getting the treatment. So, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted.